Natural Approach in English Classes in Primary Schools: Teachers' Perception and Implementation - Giri, I.G.E.P.; Artini, L. P.; Padmadewi, N. N. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2018)
This study aimed at investigating teachers’ perceptions about natural approach in teaching English for young learners and its implementation in public primary schools in Gianyar Regency, particularly on teachers’ perceptions on natural approach in teaching English for young learners, how the English teachers implement naturalistic values in teaching English as a foreign language in Gianyar regency, and teachers’ perceptions about naturalistic values for young learners related to the strategies in teaching English as a foreign language in classroom. The subjects of the study were 3 English teachers in 3 different public elementary schools in Gianyar Regency. The research design of the study was mixed methods. This study used three instruments: observation sheets, questionnaires, and interviews. The observation sheet was used to find out how teachers implemented the naturalistic values in teaching English for young learners. The questionnaire was used to find out teachers’ perceptions on natural approach and the interview was used to find out how teachers’ perceptions related to their strategies in teaching English for young learners in their classrooms. This study showed that the relation between teachers’ perceptions and the implementation found that there were few results indicated inconsistency between both of them. The data were also supported by the result of interviews.